PENGARUH PENGGUNAAN GADGET TERHADAP POLA PIKIR SISWA KELAS VIII SMP NEGERI 2 ULAWENG KECAMATAN ULAWENG KABUPATEN BONE - Abdullah, Achmad Dahlan (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This research is a quantitative descriptive study that aims to determine the effect of using gadgets on the mindset of class VIII students of SMP Negeri 2 Ulaweng, Ulaweng District, Bone Regency. The population in this study were all class VIII students of SMP Negeri 2 Ulaweng, Ulaweng District, Bone Regency and the sample was all students of class VIIIA SMP Negeri 2 Ulaweng, Ulaweng District, Bone Regency with a total of 30 students consisting of 17 male students and 13 female students. Data collection techniques were carried out using three methods, namely, questionnaires (questionnaires), documentation and interviews. Based on the data analysis, it was obtained an overview of the effect of using gadgets on students' mindsets, the percentage of several items including questionnaire item number 2 from 30 students, 8 people who answered